2015
DOI: 10.1002/rcm.7226
|View full text |Cite
|
Sign up to set email alerts
|

Direct detection of the anti‐cancer drug 9‐phenylacridine in tissues by graphite rod laser desorption vacuum‐ultraviolet post‐ionization mass spectrometry

Abstract: It was demonstrated that the anti-tumor drug ACPH could be directly and rapidly detected by LD/SPI-MS in biological tissues without any time-consuming pre-treatment procedure. This method could potentially be applied to the selective localization and analysis of small molecule drugs in tissues and to the study of the pharmacokinetics of new drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 51 publications
(93 reference statements)
0
4
0
Order By: Relevance
“…The DESI MS method is direct and rapid in providing molecular detail of the surfaces studied; however, it requires the development and optimization of novel ionization strategies for the ionization of tough ionizing molecules. LDI MS techniques have evolved to use nanomaterials to assist in fine-tuning the technique [103][104][105][106][107][108]; applications of this technique could certainly prove beneficial with respect to MP detection. MS-based techniques are still confronting reproducibility issues and lapses in quantification methodologies-these need to be overcome in order to fully utilize these techniques.…”
Section: Challenges and Future Perspectivesmentioning
confidence: 99%
“…The DESI MS method is direct and rapid in providing molecular detail of the surfaces studied; however, it requires the development and optimization of novel ionization strategies for the ionization of tough ionizing molecules. LDI MS techniques have evolved to use nanomaterials to assist in fine-tuning the technique [103][104][105][106][107][108]; applications of this technique could certainly prove beneficial with respect to MP detection. MS-based techniques are still confronting reproducibility issues and lapses in quantification methodologies-these need to be overcome in order to fully utilize these techniques.…”
Section: Challenges and Future Perspectivesmentioning
confidence: 99%
“…Quantitative analysis showed that the present methodology was available to MB of ~0.1 nmol in the mouse kidney slice. A similar L2MS system with a few modifications to the vacuum chamber was later applied to detecting an anticancer drug 9‐phenylacridine in the kidney of mice (Liu et al, 2015) and proflavine in rat whole blood (Chen et al, 2017a), indicating the potential of VUV L2MS in pharmacokinetic study.…”
Section: L2ms In Bioapplicationsmentioning
confidence: 99%
“…Numerous analytical techniques have been employed in forensic laboratories to comprehensively analyse a broad range of drugs in complex samples, usually based on the separation techniques gas chromatography-mass spectrometry (GC-MS) [1] and liquid chromatography-mass spectrometry (LC-MS), although direct MS analysis approaches have also been proposed, where the sample is analysed directly by the use of MS without prior chromatographic separation [2,3]. GC-MS has proven to be a reliable technique for drug analysis because of its high selectivity, sensitivity and the possibility of positive identification provided by drug MS libraries.…”
Section: Introductionmentioning
confidence: 99%